Comparison of antibacterial activity of both seeds and leaves ethanol extract of avocado (Persea americana Mill.) against Streptococcus mutans: Perbandingan aktivitas antibakteri ekstrak etanol biji dan daun alpukat (Persea americana Mill.) terhadap Streptococcus mutans - Vinna Kurniawati Sugiaman; Beby Tara Calosa; Natallia Pranata (Makassar Dental Journal PDGI Makassar, 2023)
The bacteria that play a role in initiating caries is Streptococcus mutans. Avocado seeds (Persea americana Mill.) contain poly-phenols that function as an antimicrobrial and anti-inflammatory, while avocado leaves contain flavonoid, alkaloid, tannin, and saponin that function as an antibacterial. This laboratory experimental study with a post-test-only control group design, is aimed to determine the effect of ethanol extracts of avocado leaves and seeds on the growth of S.mutans; comparing the avocado leaf ethanol extract group and the avocado seed group with concentrations of 50%, 25%, 12.5%, 6.25%, and 3.125% grown on BHI-B media. Positive control was chlorhexidine and negative control was DMSO. The results showed that the minimum inhibitory concentration (MIC) of 70% ethanol extract of avocado leaves and seeds against S.mutans was a concentration of ≤ 50%, while the minimum kill concentration (MKC) of extracts was above 50%. One-way Anova analysis results also showed that F= 28.882 and significant value of 0.000 (sig<0.05) so it can be concluded that there weas a different effect on the consentration of ethanol extract of avocado leaves 2.5 μg/mL and the concentration of ethanol extract of avocado seeds 12.6 μg/mL on the num-ber of S.mutans colonies.